2021
DOI: 10.1097/hmr.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

The organizational and environmental characteristics associated with hospitals’ use of intensivists

Abstract: BackgroundAs large numbers of coronavirus disease 2019 (COVID-19) patients were admitted to intensive care units (ICUs) in 2020 and 2021, the United States faced a shortage of critical care providers. Intensivists are physicians specializing in providing care in the ICU. Although studies have explored the clinical and financial benefits associated with the use of intensivists, little is known about the organizational and market factors associated with a hospital administrator’s strategic decision to use intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Other potential reasons include higher compensation than several other internal medicine subspecialties ( 16 ). Finally, PCCM likely provides broad career opportunities for fellows in the future, given the shortage of intensivists in the United States ( 17 ). The increasing interest in PCCM is likely driven by the increasing number of U.S. DO and IMG applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential reasons include higher compensation than several other internal medicine subspecialties ( 16 ). Finally, PCCM likely provides broad career opportunities for fellows in the future, given the shortage of intensivists in the United States ( 17 ). The increasing interest in PCCM is likely driven by the increasing number of U.S. DO and IMG applicants.…”
Section: Discussionmentioning
confidence: 99%
“…The Resource Dependence Theory asserted that organisations were intricately intertwined with their external environments and depended on these external resources to effectively accomplish their organisational goals (Kulkarni et al, 2023;Ozturk, 2021). Organisations endeavoured to mitigate environmental uncertainties and sustain their operations through proficient management and control of vital resources (Amanda Pinta et al, 2022;Liddle et al, 2022). By employing the Resource Dependence Theory framework, the research findings revealed a discernible pattern of reliance on external resources and the subsequent impact on performance and efficiency measures, namely a discrepancy in hospital finance systems occurred when the desired output exceeds the actual value.…”
Section: Discussionmentioning
confidence: 99%
“…There were multiple issues that put health systems under strain despite previous activities in the framework of pandemic preparedness. They mostly related to the pre-existing shortages of staff in the health system entry points, especially in primary care [18], as well as shortages of staff in infectious disease management and critical care units (e.g., intensive care doctors and nurses as well as anaesthetists) [19][20][21][22][23][24][25]. Consequently, health systems became overwhelmed quickly by big numbers of acute patients with severe respiratory problems [26,27].…”
Section: Pandemic Preparednessmentioning
confidence: 99%